Skup od razlicijeh pjesni slovinskijeh pjevaoca dubrovačkijeh - Gundulić, Ivan Šiškov; Gleđević, Antun; Đurđević, Ignjat; Pucić-Soltanović, Vice (1770)
Gundulićevi tekstovi [Ivan Šiškov Gundulić, u. 1720.]: Oton (2r-43r); Suze Radmilove (211v); Nestavnost u ljubavi (212r-213r)